Revascularization in Stable Coronary Disease: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Sultana, Nushrat; Ha, Francis J.; White, Anthony; Brown, Adam J.; Nerlekar, Nitesh (International Journal of Angiology, 2025)
The optimal management strategy for stable coronary artery disease (CAD) remains contentious. While revascularization benefits acute coronary syndromes, its role in stable CAD compared with medical therapy (MT) is less clear. This systematic review and meta-analysis evaluated the safety and efficacy of coronary revascularization (percutaneous coronary intervention [PCI] or coronary artery bypass grafting [CABG]) versus MT in patients with stable CAD. A systematic search identified randomized trials comparing revascularization with optimal MT in stable CAD. Trials included documented CAD via angiography and excluded acute coronary syndromes. The primary safety endpoint was all-cause mortality, non-fatal myocardial infarction (MI), and stroke. The primary efficacy endpoint also included unplanned revascularization, cardiac hospitalization, and major bleeding. The secondary endpoint included the percentage free from angina. Relative risk (RR) was calculated using random-effects models. Ten trials with 14,171 participants were included. There was no difference in the primary safety endpoint (RR 0.96 [0.90–1.03], p = 0.23). The primary efficacy endpoint favored revascularization (RR 0.81 [0.69–0.96], p = 0.01), primarily driven by unplanned revascularization (RR 0.5 [0.29–0.85], p = 0.01), though with increased procedural MI risk (RR 2.21 [1.44–3.39], p < 0.001). More patients had freedom from angina with revascularization compared with MT (71.8% vs. 62.9%, p < 0.001). In stable CAD, initial revascularization did not improve outcomes for the primary safety endpoint; however, it did reduce unplanned revascularization compared with MT. More patients had freedom from angina in the revascularization arm, at the cost of increased procedural MI. Decision regarding optimal management strategy for stable CAD remains a patient-centered discussion, recognizing the largely symptomatic rather than prognostic benefit that patients derive from early revascularization.
Keywords: coronary artery disease; percutaneous coronary intervention; coronary artery bypass grafting; medical therapy; meta-analysis; randomized controlled trials